The links between climate change, disasters, migration, and social resilience in Asia: A literature review - Kayly Ober (Asian Development Bank (ADB), 2019)
This working paper was written as input for the Asian Development Outlook 2019. It reviews the literature at the intersection of disasters and migration in Asia and details the story of how disasters may affect mobility, from displacement to voluntary migration to "trapped populations." It also provides an overview of the "migration as adaptation" literature, which shows that planned and sustained movement may help individuals weather shocks and diversify income in the face of disaster, as well as the uneven outcomes of disaster-related remittances in Asia. In addition, it gives insight into predicted impacts on mobility because of climate-related disasters and delves into the likely trends. Ultimately, it aims to show the diverse ways in which disaster-related migration may affect economic growth and social resilience in Asia.
Keywords: J60; O15; Q54; 330; climate change; disasters; migration; remittances; resilience